SPIRITUALISASI PEMBELAJARAN DALAM PERSPEKTIF ISLAM: Membangun Bangsa Berkarakter di Tengah Krisis Moral melalui Spritualisasi Pembelajaran dalam Perspektif Islam - Efendi Hasibuan, Zainal (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2016)
Islamic Education in the level of human ideals aims to create faithful, righteous, and noble personality, servant of Allah SWT, vicegerent on earth, and al-Insan al-Kamil. Reality shows that objective has not done, evident from the behavior of young and old often do social misbehavior and delinquency ritual. Students like brawl, youth like consumption and rampant drug trafficking in the country, quarrels father-mother carrying a divorce, increasing divorce rate statistics in Indonesia. One of the causes is the implementation of learning that has not done such emotional aspects, affective and spiritual pupil, due to diverse problems of learning, such as learning the mechanistic, verbalistic, and textual. Conducive learning and warm situation have loaded with the values of spiritual need civilized by conception of teachers and students in learning interactions. Answering this question, spritualizing learning in terms of Islam is deemed paramount. Learning emphasizes ethics, morals, manners teachers and students will not be drug moral crisis and the main shaft to build a nation of character.